Evaluation of Nitric Oxide Activity of Torilis Leptophyllain Indomethacin Induced Gastric Ulcer in Mice - batool, Saba; Noreen, Saima; Malik, Tooba; Fatima, Javaria; Shaheen, Bushra; Qammar, Sheikh Maria (Pakistan Armed Forces Medical Journal, 2023)
Objective: To evaluate the Nitric Oxide activity of Torilis leptophylla in Indomethacin-induced gastric ulcers in mice.Study Design: Laboratory-based experimental studyPlace and Duration of Study: Pharmacology Department, University of Health Sciences, Lahore Pakistan, from Jan to Dec2016.Methodology: Thirty-six adult healthy male BALB/C mice with a weight range of 25-35 g were equally divided into six groups and designated as Group-I (Control), Group-II (Positive Control), Groups III to V (Torilis leptophylla extract trial Groups) and Group-VI (Omeprazole). Gastric ulceration was induced by a single dose of Indomethacin (20mg/kg) in Groups II–VI. The plant extract was administered in Groups III-V (100, 200, 300 mg/kg) whereas Omeprazole (3mg/kg) in Group-VI by gavage daily for three days as treatment of gastric ulceration. Nitric Oxide content was measured in gastric juice and serum of all groups by Nitric Oxide assay kit.Results: The positive Control-Group showed little Nitric Oxide in gastric juice and serum. Torilis leptophylla treated Groups (100 mg/kg, 200mg/kg and 300 mg/kg) showed significantly raised Nitric Oxide content in both gastric juice and serum than the Control Group (p